Cumulative Impacts of Tourist Resorts on Wild Reindeer (Rangifer tarandus tarandus) during Winter - Nellemann, Christian; Jordhøy, Per; Støen, Ole-Gunnar; Strand, Olav (ARCTIC, 2000)
Potential avoidance by wild reindeer (Rangifer tarandus tarandus) of high-altitude tourist resorts during winter was investigated in and near Rondane National Park in Norway. Distribution of reindeer was mapped using systematic snowmobile surveys during 1991-96 and compared with results from investigations of snow and vegetation characteristics. Maternal reindeer avoided a 10 km zone around the resort. Cows and calves increased in density from 0.6 ± 0.6 reindeer/km² at 5-10 km from the resort to 7.6 ± 2.2 reindeer/km² at 15-25 km from the resort. Bulls and yearlings were more tolerant, constituting nearly 92% of all observed animals 5-10 km from the resort. Nearly all animals avoided the zone within 5 km of the resort. There were no significant differences in distribution of lichen heath, hardness of snow, integrated ram hardness index (IRH) values, or snow depths on ridges with increasing distance from the resort. Available biomass of lichens was ca. 1200 g/m² 0-5 km from the resort and decreased to a low of ca. 250 g/m² at 15-25 km distance, a pattern that probably reflects overgrazing as a result of avoiding the tourist resort. Such avoidance implies reduced forage intake during winter, substantial reduction in available habitat, and lower productivity of the herd. The results suggest that avoidance by wild animals of sources of anthropogenic disturbance may involve long-term impacts, such as reductions in carrying capacity, that are more serious than those expected from direct physiological stress. On a étudié le comportement d'évitement des stations touristiques de haute altitude que semble manifester le renne sauvage (Rangifer tarandus tarandus) en hiver, dans le parc national Rondane même et dans ses environs, en Norvège. La distribution du renne a été cartographiée à l'aide de relevés systématiques effectués en motoneige entre 1991 et 1996, et comparée avec les résultats d'études des caractéristiques de la neige et de la végétation. Les mères rennes évitaient une zone de 10 km autour de la station. Les ...